Measuring Structured Design Quality - Didi Rosiyadi; Nana Suryana (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
Structured Design is the development of a blueprint of a computer system solution to a problem that has the same components and interrelationships among the components as the original problem. Structured Design offers a set of strategies for developing a design solution from a well-defined statement of a problem and offers a set of objective and empirically justified criteria for evaluating the quality of a given design solution with respect to the problem to be solved. Structured design is not the structure chart any more than good sculpture is a chisel. The chisel is a tool for chipping that must be used with dexterity to achieve a good result. Similarly, a structure chart is simply a tool for showing a picture of the modules in a system and their relationships to one another. One of the fundamental principles of structured design is that a large system should be partitioned into manageable modules. However, it is vital that this partitioning should be carried out in such a way that the modules are as independent as possible, this is the criterion of coupling.Keywords: Design, Structured Design, Coupling